INTERNALISASI NILAI-NILAI PENDIDIKAN AKHLAK MELALUI PROGRAM TAHFIDZ AL-QUR’AN ( JUZ AMMA) DI SMP NEGERI 9 MALANG - Muhammad Asrofi Awali Mursalin; Nur Hasan; Dzulfikar Rodafi (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Morality is a matter that must be internalized to students, not only in learning, to show a good moral attitude towards others, it must be internalized through activities, one of which is through the Al-Qur'an tahfidz program (Juz amma) in internalization needs to require processes which is very long time to get to the final point on moral attitude of morals, morals that are ready to be used and carried out in daily life, the purpose of this study is of course to find out how the process of internalizing moral education towards students in SMP Negeri 9 Malang, the approach used is a qualitative approach to find out all the phenomena that exist in the field While the presence of researchers is a necessity to collect data and participate in the field, the data used by all the actions observed and interviewed as well as related documentation and photos, data analysis techniques using data techniques. interactive data, while the validity of the data by data collection, verification and field data, the results of this study indicate that in conducting internalization of moral education values must pass through three main stages including the stage of value transformation, the stage of value transactions, and the stage of value transinternalization.